Prescriptive play therapy : tailoring interventions for specific childhood problems - Kaduson, Heidi; Cangelosi, Donna M.; Schaefer, Charles E. (New York : The Guilford Press, 2020)
'This book helps practitioners choose from the broad range of play therapy approaches to create a comprehensive treatment plan that meets the individual needs of each child. From leaders in the field, the volume provides a flexible roadmap for assessment, case formulation, and intervention for frequently encountered psychological disorders and adversities. The focus is creating a unique therapy'prescription' that is tailored to the child's presenting problems as well as his or her strengths, challenges, and developmental level. Contributors present up-to-date knowledge on each clinical problem, describe practices that have been shown to be effective, and share vivid illustrations of work with 3- to 16-year-olds and their parents'--
Includes bibliographical references and index.
Keywords: Play therapy